Security and Privacy in Smart Home Systems During Crises and Emergencies: A Systematic Literature Review - Synaepa-Addison, Thomas; Kropczynski, Jess (Proceedings of the International ISCRAM Conference, 2026)
This systematic literature review (SLR) investigates security and privacy threats, and solutions for Smart Home Systems (SHS) in crises contexts. SHSs are interconnected devices of which a breach of any one component can compromise the entire system. This SLR answers two questions: (RQ1) What are the documented security vulnerabilities and privacy risks associated with smart homes in emergency scenarios like fires or burglaries? and (RQ2) What technical or architectural solutions have been used to enhance the resilience of smart homes against security vulnerabilities and privacy risks? The analysis reports data management risks; (83.33% of articles) are most prevalent threats. Human related factors are less dominant but can jeopardize SHSs. Cryptography is mostly adopted in implementing security and privacy solutions while less studies focus on AI/ML and human practices. This research highlights the gap in crises-focused analysis, as existing studies dwell on general cyber security with no clear-cut solutions for crises